Design of Electronic Mass Balance of Gram Scale Using a Gage Strain Sensor - Muhammad Priyono Tri Sulistyanto; Kurriawan Budi Pranata; Endarko Endarko; Melania Suweni Muntini (Department of Electrical Engineering and Information Technology,Faculty of Engineering UGM, 2018)
This research is conducted by utilizing strain gage uniaxial sensor with internal resistance 120 ohms and brass cantilever beam that is to build electronic mass scale in gram level. Basically, the aim of this research is to study deflect phenomenon measured by the strain gage sensor attached in the end of brass cantilever beam. Brass material was chosen to build cantilever as its Young moudulus contanst is bigger than other materials. Whilst mass loads for analizing brass cantilever profile are calibrated by manual Ohaus mass scale (PA214 type) with 0.07 gram load variations. The test result of this electronic mass scale system gets relationship of mass load data variation versus output voltage data (from differential amplifier). The relationship between mass and voltage can be approached by polynomial formula m = 4.2372V2 – 2.4551V + 1.5606 where m in gram and V in volt, and it gets 0.07 or 7% average error (less than linear formula approach). This formula is used further for programming ADC in 8-bit microcontroller to calculate mass and the calculation is shown in LCD 16x2.